Feral cats do not play a major role in leptospirosis epidemiology on Reunion Island. (2019) - Gomard, Y.; Lagadec, E.; Humeau, L.; Pinet, P.; Bureau, S.; Da Silva, D.; Turpin, M.; Soulaimana Mattoir, Y.; Georger, S.; Mavingui, P.; Tortosa, P.
Abstract: Although previous studies have reported Leptospira carriage in kidneys and urine of cats, the role of these animals in leptospirosis epidemiology remains poorly understood. Using molecular methods, we investigated Leptospira renal carriage in 172 feral cats from Reunion Island, an oceanic geographically isolated island located in the South West Indian Ocean. Only one out of the 172 analysed specimens tested positive for Leptospira DNA through quantitative real-time polymerase chain reaction. Using this positive sample, we could obtain sequences at three Leptospira loci ( rrs2, lipL32 and lipL41 ) allowing to report for the first time Leptospira borgpetersenii naturally infecting cats. Comparisons with bacterial sequences from both acute human cases and animal reservoirs revealed similarities with Leptospira sequences previously reported on Reunion Island. However, the low prevalence (0.6%) reported herein does not support any major role of feral cats in leptospirosis epidemiology on Reunion Island, contrasting with results recently reported on another Indian Ocean Island, Christmas Island. The significance of these discrepancies is discussed.